Analysis of Nursing Process on Nasopharyngeal Cancer Patient with Peaceful End of Life Theory Approach: A Case Report - Endah Panca Lydia Fatma (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2022)
Nasopharyngeal cancer is a malignancy in the nasopharyngeal area with squamous differentiation. According to Ruland and Moore, every cancer patient has the right to get comprehensive bio-socio-spiritual care to improve quality of life by relieving pain and other sufferings and providing spiritual and psychosocial support. The writing aims to apply a peaceful end-of-life care nursing theory to the nasopharyngeal cancer patient. This writing uses a case study approach. Case studies were taken on patients with nasopharyngeal cancer treated at Cipto Mangunkusumo Hospital. Case study was taken for seven days of treatment. Patients were analyzed by using Peaceful End of Life Theory. The result showed that the main nursing problem is chronic pain. Applying the theory of the peaceful end of life is appropriate for cancer patients with palliative conditions to improve their quality of life, free from pain, increasing feelings of comfort, cherish and respect, peace, and feeling close to people who are meaningful in their lives. The conclusion is that the theoretical approach focuses on the physical problems experienced and psychological, social, and spiritual needs. Nurses are expected to be able to apply the Peaceful End of Life theoretical approach in providing nursing care to patients with cancer.